2015
DOI: 10.1242/jcs.163105
|View full text |Cite
|
Sign up to set email alerts
|

Transbilayer lipid distribution in nano scale

Abstract: There is a limited number of methods to examine transbilayer lipid distribution in biomembranes. We employed freeze-fracture replicalabelling immunoelectron microscopy in combination with lipidbinding proteins and a peptide to examine both transbilayer distribution and lateral distribution of various phospholipids in mammalian cells. Our results indicate that phospholipids are exclusively distributed either in the outer or inner leaflet of human red blood cell (RBC) membranes. In contrast, in nucleated cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 95 publications
1
116
0
1
Order By: Relevance
“…We have shown here that the PE-specific antibiotic agent Duramycin effectively inhibits the infection of many pathogenic viruses without any approved vaccines or treatments. Given the importance of PE in viral entry processes, the presumed high abundance of PE on the virions, the fact that it is not exposed on the surface of healthy cells (29), Duramycin and similar PE-binding compounds may make useful antiviral agents. Although Duramycin itself contains lanthionine and methyllantionine bridges, making it expensive to synthesize and difficult to improve, its ability to control the replication of major pathogens such as EBOV, DENV, and WNV suggests that PE is a promising target for the design of broad-spectrum antiviral therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown here that the PE-specific antibiotic agent Duramycin effectively inhibits the infection of many pathogenic viruses without any approved vaccines or treatments. Given the importance of PE in viral entry processes, the presumed high abundance of PE on the virions, the fact that it is not exposed on the surface of healthy cells (29), Duramycin and similar PE-binding compounds may make useful antiviral agents. Although Duramycin itself contains lanthionine and methyllantionine bridges, making it expensive to synthesize and difficult to improve, its ability to control the replication of major pathogens such as EBOV, DENV, and WNV suggests that PE is a promising target for the design of broad-spectrum antiviral therapies.…”
Section: Discussionmentioning
confidence: 99%
“…To further verify that the ability of TIM1 to bind PE contributes to its physiological functions, we investigated the role of PE in TIM1-mediated phagocytosis. Like PS, PE is mostly confined to the inner leaflet of the plasma membrane (28,29). To assess whether PE is exposed on the surface of apoptotic cells, we induced apoptosis in Jurkat cells by using the transcription inhibitor actinomycin D, and stained them with biotin-annexin A5 or biotin-Duramycin.…”
Section: Pe Is Exposed On Apoptotic Cells and Promotes Tim1-mediatedmentioning
confidence: 99%
“…Interestingly, PLCβ1b is enriched in the caveolae of cardiomyocytes (41). A recent freeze-fracture immunoelectron microscope study reported an association of both PIP 2 and PE to the edge of the caveolae at the plasma membrane (25). It is well established that the heterotrimeric G protein Gα q -subunit activates PLCβ-lipase (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…PLCβ1b and G protein subunit Gαq, which directly activates PLCβ, are reported to localize to the caveolar fraction (37). Previously, we showed that PE and PIP 2 were accumulated at the cytoplasmic leaflet of the edge of caveolar membranes (25). To address the role of PLCβ1 in caveolae formation, we compared the ultrastructures of the plasma membrane in control and PLCβ1 knockdown Swiss 3T3 cells.…”
Section: Overexpression Of Plcβ1b and The C-terminal Fragment Inducementioning
confidence: 99%
See 1 more Smart Citation